Peningkatan Hasil Belajar IPA melalui Media Augmented Reality pada Materi Bagian Tumbuhan bagi Peserta didik Tunarungu Kelas VII di SLBN Wonogiri - Novita Ratna Dewi; Muhamad Bagus Waloyo Jati; Ratih Dyah Anggraeni; Mamik Sugiarti; Tias Martika (Universitas Sebelas Maret, 2025)
This study was conducted with the aim of helping deaf students in grade VII at SLBN Wonogiri to more practically understand the material about plant parts in Natural Sciences (IPA) lessons, through the use of Augmented Reality (AR) media that presents visual and interactive learning. The study was conducted in two cycles using the Kemmis and Mc Taggart models using the stages of action planning, observation, and reflection. Data were collected through observation and learning outcome tests (pre-test and post-test). The results showed an increase in the average value from 58.33 in the pre-cycle to 66.67 in cycle I and even higher to 76.67 in cycle II. Learning completeness also increased from 33.33% to 83.33%. AR media has proven effective in helping deaf students understand abstract material through a visual and interactive approach